CHALLENGES ENCOUNTERED BY EFL STUDENTS IN COMPLETING THE STRUCTURE & WRITTEN EXPRESSION SECTION OF THE TOEFL - Mutmainnatussafiyyah; Geminastiti Sakkir; Fauzan Hari Sudding Sally (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
The purpose of this study is to identify the challenges encountered by EFL students in completing the Structure & Written Expression section of the TOEFL. This study employed a mixed-method explanatory design, collecting data through online questionnaires and semi-structured interviews. The participants of this study were undergraduate students from the English Department of Universitas Negeri Makassar. The findings revealed several challenges including insufficient preparation, limited vocabulary, difficulties with grammatical concepts such as parallelism, inversion, and reduced clauses, poor time management, low self-confidence, and a lack of motivation. These results highlight the need for more targeted TOEFL preparation programs and offer insights for educators and institutions to improve support for EFL learners aiming to succeed in high-stakes English proficiency tests.